Diminishing trades in Singapore : the impact of Singapore's urban planning and economic-driven policies on traditional Chinese provision shops, 1950s-1990s - Kang, Kai Yu (Nanyang Technological University, 2021)
The Provision Shop holds a special place in the hearts of many Singaporeans, especially those who lived through the kampong days till the 1980s. This landmark goes beyond its role as a store that sells essentials to the locals. In fact, it was a “community hub” for the kampong dwellers to hang out, and it was also a well-recognised “family affair” for those in the provision shop industry. However, this once-valued form of business is now a diminishing trade. We should recognise that its decline coincided with Singapore’s rapid urban planning and economic developments. It is interesting to note that little literature discussed the provision shop trade despite its prominence in Singapore society. As such, this paper intends to unveil the under-researched history of the traditional Chinese provision shops in Singapore. In particular, this paper will look at how the state’s urban planning and economic-driven policies reshaped the provision shops’ “place” in Singapore’s retail landscape, in the community, and within households from the 1950s-1990s, consequently leading to the loss of the old traditions in the business and its disappearing role as the primary goods provider for the locals as well as, its rapidly waning sales.